From silence to justice: implications for persons with little or no functional speech accessing the criminal justice system - White, Robyn (Acta criminologica, 2018)
Accessing the criminal justice system is a basic human right protected internationally by the Convention on Rights of Persons with Disabilities (CRPD). However, one group within the broader disability sphere who finds accessing the criminal justice system particularly challenging is those with little or no functional speech (LNFS), as they cannot rely on spoken language to meet their needs. The aim of this research was to identify the factors that assist persons with LNFS, who had been victims of sexual crime, to access the criminal justice system in accordance with the contextual factors listed in the International Classification of Functioning, Disability and Health (ICF). Twenty-five participants took part in the research. A qualitative research design was used and three semi-structured in-depth interviews and three focus groups were conducted. A conventional qualitative analysis was used to identify themes. The findings suggested that although persons with LNFS are particularly vulnerable victims of sexual crime, personal and environmental factors can be facilitated to successfully access the criminal justice system. Our research suggests the development of a Disability Resource Toolkit to be used as a guideline and best practice model to ensure equal access to the criminal justice system for persons with LNFS.